Microscopic strength of silicon particles in an aluminium–silicon alloy - Mueller, M.G.; Fornabaio, M.; Žagar, G.; Mortensen, A. (Acta materialia, 2016)
A microscopic three-point bending test that measures the strength of faceted particles of high aspect ratio is developed and used to probe individual coarsened plate-like silicon particles extracted from the eutectic Al-12.6%Si alloy. Focused ion beam milling is used in sample preparation; however, the tapered beam cross-section and multistep preparation procedure used here ensure that the particle surface area subject to tension in mechanical testing is free of ion beam damage. Results show that coarsened silicon particles in aluminium can reach strength values on the order of 9 GPa when they are free of visible surface defects; such high strength values are comparable to what has been reported for electronic-grade silicon specimens of the same size. By contrast, tests on eutectic silicon particles that feature visible surface defects, such as pinholes or boundary grooves, result in much lower particle strength values. Reducing the incidence of surface defects on the silicon particles would thus represent a potent pathway to improved strength and ductility in 3xx series aluminium casting alloys. [Display omitted]